Case report: Personalizing the use of trazodone in real-world patients: a study of three cases of depression with comorbidities - Rosso, Gianluca; Benatti, Beatrice; Pettorruso, Mauro; Sampogna, Gaia; Tomasetti, Carmine (Frontiers in Psychiatry, 2024)
Depressive disorders are leading contributors to global mental health-related burden, and they represent a challenge for real world clinicians, due to the low rates of remission although the high availability of treatments. Often, depression shows in the contexts of multiple chronic comorbidities, thus requiring a precise and accurate management of pharmacological treatments to avoid interactions and side effects. These criticalities call for the need of new strategies of treatment, which may include new insights in the pharmacological properties of currently available antidepressant drugs, to enhance their efficacy in the different contexts in which depression may arise. Trazodone is the prototype of the serotonin antagonist/reuptake inhibitor antidepressants (SARIs). Due to the malleability granted by its multiple formulations, trazodone is frequently used to treat depression, both as add-on to other antidepressants and as monotherapy, with satisfying results. Moreover, its tolerability makes it one the most prescribed antidepressant in patients with poly-treated comorbid medical illness, especially in the elderly. Herein, a case series has been presented, regarding the use of trazodone in patients with complex comorbid diagnoses or distressing side effects. Each of the three cases has been discussed in three specific Round Tables, involving expert clinicians in the fields of Psychiatry, Neurology, General Practice, and Geriatrics using the Nominal Group Technique. The ideas collected have been used to integrate the cases and the discussion with the intent of facilitating accessibility to the widest audience of physicians and clinical workers in different clinical practice contexts. The final aim of this paper is to promote an increasingly personalized use of trazodone in real-world patients with depression.